Suggested insulin regimen for pregnant women with diabetes who wish to fast in Ramadan - Yahaya, Ahmad Shuib; Ibrahim, Adibah; Othman, Mohd Shukri; Ismail, Mohd Pazudin (International Islamic University Malaysia, 2018)
Introduction: Pregnant women are among those who are exempted from Ramadan fasting. Despite that, many pregnant women had chosen to fast despite understanding the risk of complications especially hypoglycaemia. In Hospital USM (HUSM), an insulin regime for pregnant women who wish to fast was designed based on expert opinion of obstetricians, but its safety and efficacy are yet to be determined. Objective: To determine the safety and efficacy of the formulated insulin regime using subcutaneous Actrapid® and Insulatard® amongst pregnant women with diabetes who fast in Ramadan. Methodology: Pregnant patients with diabetes on insulin who wish to fast during Ramadan were invited to participate in the study. The total daily dose of insulin requirement prior to Ramadan was divided 3 parts; 2/3 for iftar (sunset meal) and 1/3 for sahur (pre-dawn meal). For each timing, 2/3 of the calculated dose was given as short-acting insulin Actrapid® and remaining 1/3 as intermediate-acting insulin Insulatard®. Three patients were monitored in the ward while fasting for two days. Blood glucose checked eight times a day. Following that, eight patients were followed up during Ramadan fasting with this regime. Weekly blood sugar profile (BSP) was taken and glycaemic control evaluated. Results: All patients were able to fast without any hypoglycaemic episode, both during in-patient study and during out-patient Ramadan fasting. Mean daily blood glucose per day for in-patient monitoring was 7.3 mmol/l with the lowest being 4.56 mmol/l in the afternoon. During Ramadan fasting, average glucose level was higher (6.79 mmol/l) compared to prior to Ramadan value (5.67 mmol/l) (p> 0.05). However, improvement of glycaemic control was observed towards end of Ramadan. Conclusion: Pregnant women with diabetes treated with insulin can fast safely during Ramadan using the suggested insulin regime with improvement of glycaemic control observed at the end of Ramadan.